2017
DOI: 10.1053/j.gastro.2016.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Cells in Colon Cancer

Abstract: Mesenchymal cells in the intestine comprise a variety of cell types of diverse origins, functions, and molecular markers. They provide mechanical and structural support and have important functions during intestinal organogenesis, morphogenesis, and homeostasis. Recent studies of the human transcriptome have revealed their importance in the development of colorectal cancer, and studies from animal models have provided evidence for their roles in the pathogenesis of colitis-associated cancer and sporadic colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 172 publications
2
138
0
1
Order By: Relevance
“…Tumors cells may support tumor growth by educating the surrounding fibroblasts, which are referred to as CAFs 8, 37, 38 . On the other hand, a recent study reported that surface expression of CD10 and GPR77 may be markers of CAFs that mediate chemotherapy resistance in human cancer through IL-6 and IL-8 production 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors cells may support tumor growth by educating the surrounding fibroblasts, which are referred to as CAFs 8, 37, 38 . On the other hand, a recent study reported that surface expression of CD10 and GPR77 may be markers of CAFs that mediate chemotherapy resistance in human cancer through IL-6 and IL-8 production 10 .…”
Section: Discussionmentioning
confidence: 99%
“…These stromal cells organize the tissue architecture, and have recently been revealed to play crucial roles in regulating immune responses, tissue repair, and tumor development 3,4,5 . Recent studies have focused on fibroblasts that can support tumor growth, termed cancer-associated fibroblasts (CAFs) 6,7,8 . In a very recent study, single-cell RNA-sequencing (scRNA-seq) was performed to analyze colon biopsies from healthy individuals and ulcerative colitis (UC) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, materials and methods can be optimized to generate normal or aberrant iPSC lines for the purposes of regenerative medicine or cancer research/therapy. Cancer tissues comprise (pre-) cancer (stem) cells, pre-metastatic cancer cells, stromal cells (such as mesenchymal stem cells, cancer-associated fibroblasts[15,16,24] and tumor endothelial cells) and immune cells (such as tumor-associated macrophages[25], dendritic cells[26] and tumor-infiltrating T cells[23]). Therefore, such a cell-derived iPSC line might be useful for immune-cell therapy[27] with cellular vaccines[28], dendritic cells[29-32] or tumor antigen-specific cytotoxic T cells[23], in addition to the development of models of carcinogenesis[33-35] and drug discovery tools[36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The American Journal of Pathologyajp.amjpathol.org cancer. 107 Recent studies are beginning to suggest possible differences in the activation of stem cellelike self-renewal pathways in colon cancer based on race with a focus on the role of specific microRNAs. 108e111 Like breast cancer, recent studies are beginning to reveal differential signatures and influences of inflammatory pathways in prostate cancer 112e114 and the role of EMT in the generation and support of the stem cell niche.…”
Section: Inflammation Epithelial and Mesenchymal Plasticity Convergementioning
confidence: 99%